Immunologic Gene Sets Reveal Features of the Tumor Immune Microenvironment and Predict Prognosis and Immunotherapy Response: A Pan-Cancer Analysis - Pan, Hongda; Pan, Jingxin; Li, Pei; Wu, Jianghong (Frontiers in Immunology, 2022)
In the treatment of cancer, anti-programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) immunotherapy has achieved unprecedented clinical success. However, the significant response to these therapies is limited to a small number of patients. This study aimed to predict immunotherapy response and prognosis using immunologic gene sets (IGSs). The enrichment scores of 4,872 IGSs in 348 patients with metastatic urothelial cancer treated with anti-PD-L1 therapy were computed using gene set variation analysis (GSVA). An IGS-based classification (IGSC) was constructed using a nonnegative matrix factorization (NMF) approach. An IGS-based risk prediction model (RPM) was developed using the least absolute shrinkage and selection operator (LASSO) method. The IMvigor210 cohort was divided into three distinct subtypes, among which subtype 2 had the best prognosis and the highest immunotherapy response rate. Subtype 2 also had significantly higher PD-L1 expression, a higher proportion of the immune-inflamed phenotype, and a higher tumor mutational burden (TMB). An RPM was constructed using four gene sets, and it could effectively predict prognosis and immunotherapy response in patients receiving anti-PD-L1 immunotherapy. Pan-cancer analyses also demonstrated that the RPM was capable of accurate risk stratification across multiple cancer types, and RPM score was significantly associated with TMB, microsatellite instability (MSI), CD8+ T-cell infiltration, and the expression of cytokines interferon-γ (IFN-γ), transforming growth factor-β (TGF-β) and tumor necrosis factor-α (TNF-α), which are key predictors of immunotherapy response. The IGSC strengthens our understanding of the diverse biological processes in tumor immune microenvironment, and the RPM can be a promising biomarker for predicting the prognosis and response in cancer immunotherapy.